Teaching reading in Rukwangali in four Grade 3 Namibian classrooms : a case study - Siyave, Theresia Nerumbu (Rhodes University, Faculty of Education, Department of Education, 2011)
This study aims to explore four grade 3 teachers' understanding of teaching reading in Rukwangali, a home language in Namibia in Kavango region and to observe the strategies they use as well as the activities they set for their learners. During my School Based Studies (SBS), I noticed that learners were not reading with understanding. My interest was also stimulated by a study carried out in Namibia that found that the literacy levels for Namibian learners were poor compared to those of other African countries. This is a qualitative case study carried out within an interpretive paradigm. It seeks to understand the meaning that people attached to human actions. I selected the participants purposefully and in terms of convenience, as all three schools selected are situated in Rundu, the town in which I work as a college lecturer. The research tools I employed were semi-structured interviews, document analysis, classroom observation, and stimulated recall discussions on the lessons I observed. I used a variety of methods to triangulate data and enhance validity. This study reveals that teachers use multiple methods to teach reading. These methods include phonics and syllabification to help struggling learners to decode difficult and long (polysyllabic) words and the look-and-say method for whole word recognition and meaning making at word and sentence level. In addition, they also use the thematic approach to teaching and learning to expand learners' vocabulary and enhance their understanding of the texts they read and to make their lessons learnercentred. However, the problems of language, lack of reading books written in Rukwangali and large class sizes constrain the teachers from teaching in a more learner-centred way. Therefore, the study gives some tentative recommendations to remedy this situation.
Keywords: Reading (Elementary) -- Namibia; Reading teachers -- Training of -- Namibia; Kwangali language -- Study and teaching (Elementary) -- Namibia; Literacy -- Study and teaching (Elementary) -- Namibia; Native language and education -- Study and teaching (Elementary) -- Namibia